2015
DOI: 10.1021/acs.jpcc.5b10176
|View full text |Cite
|
Sign up to set email alerts
|

What Can Be Learned from Magnetic Field Effects on Singlet Fission: Role of Exchange Interaction in Excited Triplet Pairs

Abstract: Magnetic field effects (MFEs) on singlet fission were studied by observing fluorescence from organic crystal of 1,6-diphenyl-1,3,5-hexatriene under magnetic fields of up to 5 T. We found anomalous MFE dips at magnetic fields higher than 2 T, in addition to the known MFEs which saturated around 1 T. The observed results were analyzed by using the stochastic Liouville equation (SLE) in which a distance-dependent exchange interaction (J) in triplet pair, hopping of triplet, and geminate fusion in contacted triple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
70
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 25 publications
4
70
0
2
Order By: Relevance
“…Despite their key role in light-emitters and harvesters, triplet pairs have only recently been discovered to form exchange-coupled states [13][14][15][16][17]. We start by outlining how such states can be selectively addressed to provide a site-specific measurement of their exchange interactions and associated optical spectra.…”
Section: Selectively Addressing Exchange-coupled Tripletsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite their key role in light-emitters and harvesters, triplet pairs have only recently been discovered to form exchange-coupled states [13][14][15][16][17]. We start by outlining how such states can be selectively addressed to provide a site-specific measurement of their exchange interactions and associated optical spectra.…”
Section: Selectively Addressing Exchange-coupled Tripletsmentioning
confidence: 99%
“…At these field positions, bright singlet pair states become hybridized with a dark triplet or quintet pair-state, manifesting as a resonant reduction in the relevant PL spectral window (Fig. 1C ) [16][17][18].…”
Section: Selectively Addressing Exchange-coupled Tripletsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a TP, spin states and spin dynamics are influenced by magnetic fields [1][2][3][4]37,38 . In the case of a correlated TP in which there was a distinct exchange interaction, we recently reported that singlet fission from an organic crystal of 1,6-diphenyl-1,3,5-hexatriene (DPH) showed clear magnetic field effects (MFEs) at magnetic field strengths of 0-5 T 38 .…”
mentioning
confidence: 99%
“…In the case of a correlated TP in which there was a distinct exchange interaction, we recently reported that singlet fission from an organic crystal of 1,6-diphenyl-1,3,5-hexatriene (DPH) showed clear magnetic field effects (MFEs) at magnetic field strengths of 0-5 T 38 . These MFEs on the fluorescence of DPH could be explained by the level crossing of correlated TP.…”
mentioning
confidence: 99%